Correlation studies on equity markets using linear regression model - Malaysia, developing and developed markets - Haron, Razali; Zainal Abidin, Sazali (Faculty of Business Management Universiti Teknologi MARA and UPENA, 2006)
The specific objective of this paper is to generate and analyze the average correction coefficient between Malaysian equity market and other selected countries equity markets during 17 year period from January 1987 to December 2003.The study employs Linear Regression Model to determine the correlation coefficients between Malaysia and other countries. The period of 17 years is further divided into 13 different sub-periods divided by pre, during and post crisis in order to study the differences in pattern of average correlation coefficients during the sub-periods. The study found that average correlations increase during the non-crisis periods as compared to crisis periods. The study also divided the group of countries according to developed countries and emerging countries to analyze the correlation coefficients between Malaysian market and markets of those groups of countries. Malaysian market is found to be more correlated with the emerging market than the developed market. The study also analyses the evolution of correlation of the Malaysian market and other countries over time. From an investment point of view of Malaysian investors, international portfolio diversification still offers diversification benefits due to instability in correlations over time.